Effect of caldesmon mutations in the development of zebrafish embryos - Virtanen Verneri; Paunu Kreetta; Niva Saana; Sundvall Maria; Paatero Ilkka (United Kingdom, 2025)
Cancer is a profound medical concern and better treatments are needed for cancer patients. Therefore, new cancer targets are constantly being studied. These targets need not only be relevant for cancer progression, but their modulation needs to be tolerated reasonably well by the host. Caldesmon is one of these proposed novel targets for cancer therapy. Therefore, we analyzed effects of caldesmon mutations in normal development using genetically modified zebrafish embryos. We analyzed mutations in both zebrafish caldesmon genes, cald1a and cald1b and analyzed effects of either mutation alone or as in combination in double homozygous embryos using molecular, morphological and functional analyses. The effects of caldesmon mutations were mild and the gross development of zebrafish embryos was normal. The caldesmon mutant embryos had, however, alterations in response to light-stimulus in behavioural assays. Taken together, the effects of caldesmon mutations in the development of zebrafish embryos were reasonably well tolerated and did not indicate significant concerns for caldesmon being a potential target for cancer therapy.